Exploration of differentiated learning and its impact on students’ social skills in elementary schools - Supriati, Supriati; Sriyanto, Sriyanto (Indonesian Research Journal in Education |IRJE|, 2026)
Differentiated learning is increasingly recognized as an approach that addresses students’ diverse learning needs while encouraging active participation in the classroom. This study explored the implementation of differentiated learning and its influence on students’ social skills at State Elementary School 3 Kemawi, Banyumas Regency, Indonesia. Using a qualitative case study design, data were collected through classroom observations, semi-structured interviews, and document analysis. The participants consisted of two classroom teachers and six students from the third and sixth grades. The findings revealed that teachers implemented differentiated learning through diagnostic assessment, flexible instructional planning, and modifications to content, process, and product. Students responded positively to these practices and demonstrated improvements in peer relationships, self-management, academic participation, compliance, and assertion skills. The study suggests that differentiated learning can support both academic engagement and social development by creating learning environments that promote collaboration, participation, and respect for individual differences.